Work-related Variables and Job Satisfaction of Secondary Mathematics Teachers - Molano, Raymund R (ASEAN Multidisciplinary Research Journal, 2020)
Teacher satisfaction should be a concern for those who desire effective schools and this is one the premises this study is grounded on. The researcher believes that for schools to be effective, administrators need to look at some personal attributes of teachers and its relationship to the level of job satisfaction of these teachers. This study focused on determining the level of job satisfaction of secondary mathematics teachers in Second Congressional District of Pangasinan and whether this level is affected by some work – related variables. Based on the data gathered and results generated, majority of the teacher respondents are female, married, relatively new in the present school where they teach, are not new in the teaching profession, holders of a bachelor’s degree, teaches three to four subjects. It was also found in the study that the teachers are generally satisfied with their job and they are very satisfied with the work-related personal factors in their job as teachers. They are also least satisfied with the factor on salary or compensation they receive as teachers while they are most satisfied with the factor on their attitude towards work and their personality as a teacher. Moreover, it was found in the study that of the seven work – related variables considered in this study, the level of job satisfaction of the teachers is dependent on sex and salary. As a result of the findings and conclusions of this study, it was recommended that school administrators must put into consideration sex and salary in giving teaching assignments and tasks to their teachers. They must also continually monitor their teachers’ job satisfaction. Furthermore, policy makers should put into consideration the work – related variables of teachers in securing their job satisfaction.